Impacts of direct and indirect tax reforms in Vietnam: A CGE analysis - Keshab Bhattarai; Dung Thi Kim Nguyen; Chan Van Nguyen (Economies, 2019)
The study applies a multi-sector multi-household static computable general equilibrium (CGE) tax model to assess the economy-wide impacts of taxes in Vietnam. It examines two tax reform scenarios based on the tax reform plan proposed by the Vietnam Ministry of Finance. The first scenario is increasing the value-added tax (VAT) rate to 12% from the current 10% rate. The second scenario relates to setting a competitive corporate income tax (CIT) rate to the lowest rate in ASEAN (Associations of South East Asian Nations) countries by reducing it from 20% to 17%. Correction of current tax distortions will have positive impacts on labour supply, utility, consumption, output, and welfare of households as they reallocate resources from more to less productive sectors of the economy. The CGE model allows for the finding of the macroeconomic and sectoral effects on prices and outputs, as well as on welfare of households. While this study contributes to the literature on the CGE model for the Vietnam economy, it is a small step for finding the optimal tax structure in Vietnam. It recommends that the Vietnam government should increase the standard VAT rate to 12% and reduce CIT rate to 17% to shift the tax burden from capitalists to consumers.
Keywords: H3; E62; C68; D58; 330; tax reform; general equilibrium; tax analysis; Vietnam